2016
DOI: 10.1587/transinf.2016pap0011
|View full text |Cite
|
Sign up to set email alerts
|

Fully Parallelized LZW Decompression for CUDA-Enabled GPUs

Abstract: SUMMARYThe main contribution of this paper is to present a workoptimal parallel algorithm for LZW decompression and to implement it in a CUDA-enabled GPU. Since sequential LZW decompression creates a dictionary table by reading codes in a compressed file one by one, it is not easy to parallelize it. We first present a work-optimal parallel LZW decompression algorithm on the CREW-PRAM (Concurrent-Read Exclusive-Write Parallel Random Access Machine), which is a standard theoretical parallel computing model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Gompresso LZ77-based 8 LZW GPU implementation of LZW 9,23 shown in Funasaka et al 17 For evaluating the performance including the data compression ratio and the running time for decompression, we have used a data set in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gompresso LZ77-based 8 LZW GPU implementation of LZW 9,23 shown in Funasaka et al 17 For evaluating the performance including the data compression ratio and the running time for decompression, we have used a data set in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Quite recently, we have presented GPU implementation of LZW decompression with code-wise parallel. 17 The idea is to create a dictionary by parallel pointer traversing. Because pointer traversing is code-wise parallel, LZW decompression on the GPU is much faster than CULZSS decompression.…”
Section: Lossless Data Compression and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Funasaka et al have demonstrated multiple approaches for efficient decompression facilities on GPUs with the goal of increasing the data transfer efficiency either from host main memory or from non‐volatile storage. The approaches are using different compression algorithms, including the heavy‐weight LZW algorithm 37 as well as custom light‐weight strategies such as the light loss‐less data compression (LLL) 38 and adaptive lossless data compression (ALL) 6 approaches. Especially the custom algorithms LLL and ALL optimized for efficient decompression on GPUs can outperform CULZSS 25 and their GPU‐based LZW implementation 37 significantly.…”
Section: Related Workmentioning
confidence: 99%
“…The approaches are using different compression algorithms, including the heavy‐weight LZW algorithm 37 as well as custom light‐weight strategies such as the light loss‐less data compression (LLL) 38 and adaptive lossless data compression (ALL) 6 approaches. Especially the custom algorithms LLL and ALL optimized for efficient decompression on GPUs can outperform CULZSS 25 and their GPU‐based LZW implementation 37 significantly. Rozenberg et al 39 presented a library of GPU‐based decompressors for many established light‐weight compression algorithms.…”
Section: Related Workmentioning
confidence: 99%